Integrasi Perbankan Syariah dan Fintech Syariah Pengembangan UMKM - Kamaruddin; Nasrullah Bin Sapa; Hasbiullah Hasbiullah; Trimulato Trimulato (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
The research objective is to describe the development of Islamic bank financing for SMEs, the development of sharia fintech, and the form of integration between sharia banking and the development of sharia fintech for the development of SMEs. The research method used is qualitative, related to sharia bank financing. Field research on two sharia bankings in the city of Makassar. Primary data sources through direct interviews, and secondary data from data presented from the financial services authority (OJK). Data collection techniques through interviews, documentation, and literature studies from several sources. The data analysis technique used is descriptive qualitative, by describing the development of sharia banking financing product to SMEs sector, the development of sharia fintech, and the form of integration of sharia banking and sharia fintech in the development of SMEs. The results of this study show that the development of sharia banking financing product in 2019 until the 2020 market grew by 15.93 percent, for sharia banking the type of Islamic Financing Bank (BPRS) grew 4.57 percent, while Islamic banks with the type of Sharia Business Unit (UUS) for financing trips for SMEs decreased -2.7 percent. The development of Sharia Fintech, a peer-to-peer (P2P) lending type of fintech. The number of borrower accounts increased by 325.95 percent, the number of borrower accounts in December 2019 was 18,569,123, and the number of guarantors increased by 258.56 percent with the number of loans in December 2019 of IDR 81.50 trillion. There are 12 registered sharia fintech companies. The total assets of Islamic fintech are 50,591,727,786 rupiahs. Integration between Islamic Banks and Sharia Fintech in developing SMEs needs to be carried out, to increase financial access to the public. The form of integration that can be carried out between Islamic banks and Islamic fintech is a profit-sharing scheme, which can carry out mudharabah or musyarakah contracts. SMEs may need easy access to technology services. Integration in the form of collaboration to empower SMEs.